1234 Cake!: A Count-and-Bake Book a count-and-bake book - Wright, Caroline; Oliver, Alison (New York : HarperFestival, 2021)
"Little bakers everywhere will love counting all the ingredients and steps that go into baking a cake, and then joining adults in the kitchen to practice measuring, mixing, decorating, and tasting! Featuring catchy, rhyming text, irresistible art, and a kid-friendly cake and icing recipe, this sturdy board book is perfect for story time and snack time."--Amazon.com.
Cover title.
On board pages.
New Kids Book 2022 Fall.
00-04.
P-P.
Keywords: Baking -- Juvenile fiction; Counting -- Juvenile fiction; Board books; Cake; Board books; Fiction